Atmospheric and oceanic science letters - Zhongguo ke xue yuan. Da qi wu li yan jiu suo. ([Beijing] : [Institute of Atmospheric Physics, Chinese Academy of Sciences], 2008)
Atmospheric and Oceanic Science Letters (AOSL) is an international English letters journal, which provides a forum for the publication of research letters related to all aspects of the atmospheric sciences and physical oceanography.
Description baseed on: Vol. 1, issue 1 (2008); title from PDF cover image (Taylor & Francis website, viewed on November 15, 2016).
Latest issue consulted: Vol. 12, issue 5 (2019) (viewed Sept. 5, 2019).
Keywords: Ocean-atmosphere interaction -- Periodicals; Marine meteorology -- Periodicals; Marine meteorology; Ocean-atmosphere interaction; Atmosphere -- Oceans; Electronic journals